2021
DOI: 10.1002/jpln.202100112
|View full text |Cite
|
Sign up to set email alerts
|

Potato root and leaf phosphatase activity in response to P deprivation

Abstract: Background Plants are not able to take up organically bound phosphorus (P) before it is hydrolyzed by extracellular phosphatases while intracellular phosphatases play a role in P remobilization. Aims The aim of this study was to evaluate intra‐ and extracellular acid phosphatase activity as well as root and shoot growth of two modern starch potato cultivars at different levels of P deprivation. Methods In vitro propagated potato plantlets (cultivars Kuba and Cardoso) were grown in sand and fertigated with five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…However, 'Kuba' strongly increased TRL in the LP treatment while TRL of 'Cardoso' remained constant. Since TRL of only two cultivars was observed in the previous study [ 58 ], it is difficult to draw valid conclusions from the data. Further experiments with a larger number of contrasting phenotypes are required to verify the suitability of RSA traits assessed at very early growth stages as selection criteria in plant breeding.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, 'Kuba' strongly increased TRL in the LP treatment while TRL of 'Cardoso' remained constant. Since TRL of only two cultivars was observed in the previous study [ 58 ], it is difficult to draw valid conclusions from the data. Further experiments with a larger number of contrasting phenotypes are required to verify the suitability of RSA traits assessed at very early growth stages as selection criteria in plant breeding.…”
Section: Discussionmentioning
confidence: 93%
“…Phenotype assessment at very early growth stages can only serve as selection criteria if the measured trait remains stable during development. Total root length (TRL) of the two cultivars 'Cardoso' and 'Kuba' was measured at the end of an experiment with a duration of seven weeks [ 58 ]. 'Cardoso' had a significantly higher TRL across different P-nutrition levels, which matches with the results in the HP treatment of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In a greenhouse study, a similar trend in shoot growth has been reported with a decline in the P use efficiency in shoot growth with high P applications [ 27 ]. In addition, the lack of shoot growth could be related to the plant allocating more sugars to the roots, which has been reported in potato plants grown under deficient P [ 28 ]. In this study, the same phenomenon also occurred at excessive P supply, as evident from the improved root growth ( Figure 2 B), suggesting that it occurs not only at deficient but also at excessive P. This correlated with a significant increase in Mg content from 1.25 to 3.5 mM P ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are possible alternatives to the classic ecotoxicity test, one such test being the acid phosphatase enzyme activity inhibition test which represents a potential ecotoxicity test at the molecular level [7]. The enzymatic activity (EA) of acid phosphatases can be influenced by pollutants present in the environment, inducing an inhibition of the enzymatic activity, revealing possible toxic effects of the analysed pollutants [8].…”
Section: Introductionmentioning
confidence: 99%